2018
DOI: 10.3233/bmr-169657
|View full text |Cite
|
Sign up to set email alerts
|

Relationship of work disability between the disease activity, depression and quality of life in patients with ankylosing spondylitis

Abstract: In this study, we determined that AS had a significant influence on the working conditions and the factors related to the disease had a significant correlation with work productivity. Factors related to the psychology and the disease were also correlated with the working conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
23
1
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 22 publications
5
23
1
2
Order By: Relevance
“…Age, ethnicity, disease duration, disease activity, function, quality of life and current NSAID use were included in all multivariable analyses as they were significant in at least one univariable analysis. Some of these factors – age, ethnicity, disease duration, disease activity and function – were reported to significantly affect work outcomes in other studies as well.…”
Section: Resultsmentioning
confidence: 85%
See 1 more Smart Citation
“…Age, ethnicity, disease duration, disease activity, function, quality of life and current NSAID use were included in all multivariable analyses as they were significant in at least one univariable analysis. Some of these factors – age, ethnicity, disease duration, disease activity and function – were reported to significantly affect work outcomes in other studies as well.…”
Section: Resultsmentioning
confidence: 85%
“…Studies in axSpA and ankylosing spondylitis populations have previously shown that increased disease activity was associated with presenteeism and activity impairment . Other studies have demonstrated that decreased physical function was associated with work productivity loss and activity impairment, and poorer quality of life with absenteeism, presenteeism, work productivity loss and activity impairment …”
Section: Discussionmentioning
confidence: 98%
“…TNF-α, with an intensive biological effect, is regarded as the most important factor in the development of AS and proven to be positively associated with disease activity [32,33]. We suggested the poor nutrition might also attributed to psychological disorders [12,34]. The global function might be affected after long-term low nutritional condition and inflammatory cytokine activation.…”
Section: Discussionmentioning
confidence: 94%
“…Disease activity pointing to a feature of inflammation is believed to potentially affect the multi-system functions in AS. Significant correlations were found between work productivity, daily activity, psychological status and disease activity [11,12]. Furthermore, disease activity was suggested as an increased risk of mortality [13], which might be associated with the impairment of cardiovascular system, coagulation-fibrinolytic system and microvascular function [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α, with an intensive biological effect, is regarded as the most important factor in the development of AS and proven to be positively associated with disease activity (32,33). We suggested the poor nutrition might also attributed to psychological disorders (12,34). The global function might be affected after long-term low nutritional condition and inflammatory cytokine activation.…”
Section: Discussionmentioning
confidence: 92%